1966
DOI: 10.1017/s0022172400040651
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of Clostridium welchii in the faeces of varying sections of the human population

Abstract: A method of doing viable counts of Cl. welchii has been described that gives reproducible results from faeces. By this method counts were carried out on the faeces of persons in the general population, and those associated with an outbreak of food poisoning due to Cl. welchii. There was a significant increase in viable count in those with symptoms of food poisoning. Owing to many variables, single viable counts do not appear to be useful in the laboratory diagnosis of food poisoning, but the detection of heat-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1967
1967
1991
1991

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
(18 reference statements)
2
7
0
Order By: Relevance
“…During the course of this survey none of the group A patients suffered from any form of gastroenteritis or diarrhoeal illness and the high numbers of C. perfringens carried by these patients was probably a reflexion of the normal 286 M. F. STRINGER AND OTHERS carriage situation for some elderly institutionalized or hospitalized patients. These results therefore support the findings of Yamagishi et al (1971) and Sutton (1966). If a cluster of cases of diarrhoea occur in such patients it is not unreasonable, following the laboratory examination of faecal specimens, to assume that C. perfringens food poisoning is responsible.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…During the course of this survey none of the group A patients suffered from any form of gastroenteritis or diarrhoeal illness and the high numbers of C. perfringens carried by these patients was probably a reflexion of the normal 286 M. F. STRINGER AND OTHERS carriage situation for some elderly institutionalized or hospitalized patients. These results therefore support the findings of Yamagishi et al (1971) and Sutton (1966). If a cluster of cases of diarrhoea occur in such patients it is not unreasonable, following the laboratory examination of faecal specimens, to assume that C. perfringens food poisoning is responsible.…”
Section: Discussionsupporting
confidence: 91%
“…Faecal carriage of C. perfringens has been studied primarily in relation to its diagnostic significance in the investigation of suspected outbreaks of food-borne disease, and it was soon realized that it was important to estimate the numbers of C. perfringens in faecal specimens. Sutton (1966) showed that healthy people usually carried between 103 and 104 organisms/g whereas patients in outbreaks tended to carry 105-106/g. In 1976, Yamagishi et al found that the numbers of C. perfringens in the faeces of some healthy adults in a Japanese Home for the Aged were consistently of the order of 107-109/g.…”
Section: Introductionmentioning
confidence: 99%
“…The low incidence of heat-resistant C. perfringens spores in normal feces is consistent with reports from the United States (7), the United Kingdom (4,13) and Australia (17,18), whereas Japanese workers have detected heatresistent spores in over 50% of normal stools (1).…”
Section: Resultssupporting
confidence: 89%
“…On the other hand, Sutton (1966b) investigated an outbreak of Cl. welchii food poisoning and isolated heat-resistant Cl.…”
Section: Introductionmentioning
confidence: 99%